2022
DOI: 10.3390/ijerph191912041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in Cardiovascular Clinical Trial Participation among Black Men: Black Impact

Abstract: Background: Attainment of the American Heart Association’s Life’s Simple 7 (LS7) metrics reduces cardiovascular disease (CVD) risk; yet, Black Americans have the lowest LS7 attainment among all communities, the highest rate of CVD mortality, and low clinical trial participation. Social support is positively correlated with chronic disease self-management. Here, we describe the role of social support in a single-arm pilot clinical trial of a community-based lifestyle intervention among Black American men. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Engaging key stakeholders was a critical component of community engagement, given that focusing solely on clinical trial recruitment without any input or cooperation from community members may have proven less successful [42]. Though the partnership was beneficial, many Black men queried reported that interpersonal relationships between the other men participating in the trial and members of the research team built their confidence to participate in the study [43]. For several others, this rapport spoke to the benevolent intent of the research team, which likely had an essential role in reducing the mistrust associated with clinical trials among Black men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging key stakeholders was a critical component of community engagement, given that focusing solely on clinical trial recruitment without any input or cooperation from community members may have proven less successful [42]. Though the partnership was beneficial, many Black men queried reported that interpersonal relationships between the other men participating in the trial and members of the research team built their confidence to participate in the study [43]. For several others, this rapport spoke to the benevolent intent of the research team, which likely had an essential role in reducing the mistrust associated with clinical trials among Black men.…”
Section: Discussionmentioning
confidence: 99%
“…After participants have been enrolled in the study, promoting camaraderie and fellowship becomes paramount for building trust and encouraging active participation. This imperative was acknowledged and effectively addressed in the Black Impact study through the implementation of strategies aimed at bolstering social support [43]. By organizing teams based on residence, the study encouraged regular interaction among participants, extending beyond the scheduled in-person study sessions.…”
Section: Incorporating Opportunities That Afford Comradery and Fellow...mentioning
confidence: 99%